2016
DOI: 10.3390/ma9060455
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Performance of Functionalized Graphene Nanoplatelet Aqueous Nanofluids

Abstract: The low thermal conductivity of fluids used in many industrial applications is one of the primary limitations in the development of more efficient heat transfer systems. A promising solution to this problem is the suspension of nanoparticles with high thermal conductivities in a base fluid. These suspensions, known as nanofluids, have great potential for enhancing heat transfer. The heat transfer enhancement of sulfonic acid-functionalized graphene nanoplatelet water-based nanofluids is addressed in this work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 45 publications
5
35
1
Order By: Relevance
“…In a first inspection, it is observed that in the commercial powder graphene is stacked forming domains of up to several micrometres. By studying the specimen in more detail, it is possible to differentiate several nanometre-thick laminar structures of rough surfaces, which correspond with the lamellar morphology previously reported for graphene platelets [ 44 , 45 ]. SEM technique was also combined with energy dispersive X-ray spectroscopy (EDS Oxford Inca Energy 300 SEM, Oxford Instruments, Abingdon, UK) in order to analyse the elemental composition of the dry graphene nanopowder.…”
Section: Methodssupporting
confidence: 64%
“…In a first inspection, it is observed that in the commercial powder graphene is stacked forming domains of up to several micrometres. By studying the specimen in more detail, it is possible to differentiate several nanometre-thick laminar structures of rough surfaces, which correspond with the lamellar morphology previously reported for graphene platelets [ 44 , 45 ]. SEM technique was also combined with energy dispersive X-ray spectroscopy (EDS Oxford Inca Energy 300 SEM, Oxford Instruments, Abingdon, UK) in order to analyse the elemental composition of the dry graphene nanopowder.…”
Section: Methodssupporting
confidence: 64%
“…The results show that the thermal conductivity of the base fluids and those of the nanofluids increased with temperature and the relative thermal conductivity of all nanofluids was quasi-constant with the variation of the temperature, within the experimental uncertainty. A similar trend has been previously reported in other works [ 81 , 82 , 83 ]. It is widely known that the concentration of the nanoparticles plays an important role in improving the thermal conductivity and then heat transfer of nanofluids.…”
Section: Resultssupporting
confidence: 92%
“…The edges are not flat and smooth but rounded, which may be due to the synthesis route as also pointed out in [44]. A further characterization of the studied GOnP nanoplatelets can be found in Agromayor et al [45].
Fig.
…”
Section: Methodsmentioning
confidence: 87%